Physico-chemical and biological approaches in microalgal modification for harvesting and heavy metal removal - Lapenas, Louie Anciado
Microalgal technology has been widely used for various commercial and commercial industrial applications. In this study, physico-chemical and biological approaches of microalagal modification was carried out to improve the over-all performance of microalagal technology, specifically on the field of biofuel production and bioremediation. Using manganese containing magnetic ferrite nanoparticles, Chlorella sorokiniana and Scenedesmus obliquus were harvested with high efficiency. The nanomaterials used were biocompatible making the cells viable after modification, paving way for another application. In fact, modified Chlorella sorokiniana effectively remediate even low concentrations (1-10 ppm) of Cr, Co and Ni which is one of the limitations of the conventional methods. Likewise, the manganese oxides produced by Chlorella sorokiniana grown in a manganese concentrated environment effectively remove the studied metal ions. Though, high concentration of Mn was toxic to it, Chlorella oxidized Mn to detoxify and survive.